A Discourse Analysis of Malaysia's Post- 2008 Multicultural Politics - Ahmad, Khairil Izamin (N.A., 2015)
Recent theoretical and methodological innovations have given rise to novel approaches for conducting investigations in the multitude of disciplines and topics within the social sciences. This research seeks to explore how poststructuralist theory, as one representative of these approaches, can contribute to debates surrounding multicultural politics in the Malaysian social sciences. Such debates cover the different aspects of multicultural politics in Malaysia, from trying to understand the changing nature of the country’s plural society, to trying to explore different ways to manage the multicultural society, to trying to think of the appropriate policy responses to specific problems relating to cultural or religious relations, to exploring the ‘best’ model under which people and groups who make up the multicultural society should live. It is argued in this paper that, on the one hand, participants within these debates would often veer towards the embracement of unrequired normativism and essentialism. That is to say, exchanges within such conversations would assume a form of clash of perspectives – i.e. a ‘my solution is better than yours’ situation – by which we are served with participants’ uncompromising standpoints. On the other hand, we could also face an approach which believes that complete neutrality and objectivity can be assumed in researching phenomena within the dynamics of Malaysia’s multicultural politics. According to this perspective, the job of the analyst, or the social scientist, is simply to explain these phenomena based on findings from gathered data. The poststructuralist approach to the social sciences could bridge the gap between these assumptions, by furnishing us with innovative tools to work with in both understanding the various issues surrounding multicultural politics in Malaysia, which is undoubtedly at a crossroads today, as well as in developing critical insights to present to others, without succumbing to normativism and essentialism. The result of the intervention of this paper would be a means to contribute towards the betterment of Malaysia’s multicultural society.